Comparative genomic and functional analysis of Arthrobacter sp. UMCV2 reveals the presence of luxR-related genes inducible by the biocompound N, N-dimethylhexadecilamine - Chávez-Moctezuma, Martha Patricia; Martínez-Cámara, Ramiro; Hernández-Salmerón, Julie; Moreno-Hagelsieb, Gabriel; Santoyo, Gustavo; Valencia-Cantero, Eduardo (Frontiers in Microbiology, 2022)
Quorum sensing (QS) is a bacterial cell-cell communication system with genetically regulated mechanisms dependent on cell density. Canonical QS systems in gram-negative bacteria possess an autoinducer synthase (LuxI family) and a transcriptional regulator (LuxR family) that respond to an autoinducer molecule. In Gram-positive bacteria, the LuxR transcriptional regulators “solo” (not associated with a LuxI homolog) may play key roles in intracellular communication. Arthrobacter sp. UMCV2 is an actinobacterium that promotes plant growth by emitting the volatile organic compound N, N,-dimethylhexadecylamine (DMHDA). This compound induces iron deficiency, defense responses in plants, and swarming motility in Arthrobacter sp. UMCV2. In this study, the draft genome of this bacterium was assembled and compared with the genomes of type strains of the Arthrobacter genus, finding that it does not belong to any previously described species. Genome explorations also revealed the presence of 16 luxR-related genes, but no luxI homologs were discovered. Eleven of these sequences possess the LuxR characteristic DNA-binding domain with a helix-turn-helix motif and were designated as auto-inducer-related regulators (AirR). Four sequences possessed LuxR analogous domains and were designated as auto-inducer analogous regulators (AiaR). When swarming motility was induced with DMHDA, eight airR genes and two aiaR genes were upregulated. These results indicate that the expression of multiple luxR-related genes is induced in actinobacteria, such as Arthrobacter sp. UMCV2, by the action of the bacterial biocompound DMHDA when QS behavior is produced.